Teaching the Topic of Probability of Events Using - Sharipovich , Rashidov Anvarjon; Orifovna , Azimova Dilnoza (Excellencia: International Multi-disciplinary Journal of Education (2994-9521), 2025)
Nowadays, when it comes to applying new methods or innovations in the educational process, the use of interactive methods in teaching is understood. Interactivity refers to the mutual activity of two individuals, meaning the learning process occurs through dialogue (computer interaction) or communication between the teacher and the student. Interactivity is mutual activity, action, and influence. It takes place in the interactions between the student and the teacher. The main goal of interactive methods is to create a favorable environment for the learning process, enabling students to think actively and freely. This article presents some considerations and methodological recommendations for teaching the topic "Addition and Multiplication of Probabilities. Methods for Calculating the Probability of Events" in the Mathematics curriculum of general education schools.